2006
DOI: 10.1182/blood-2006-05-025221
|View full text |Cite
|
Sign up to set email alerts
|

A novel PAX5-ELN fusion protein identified in B-cell acute lymphoblastic leukemia acts as a dominant negative on wild-type PAX5

Abstract: We report a novel t(7;9)(q11;p13) translocation in 2 patients with B-cell acute lymphoblastic leukemia (B-ALL). By fluorescent in situ hybridization and 3 rapid amplification of cDNA ends, we showed that the paired box domain of PAX5 was fused with the elastin ( IntroductionPAX5 is a member of the highly conserved paired-box (PAX) domain family of transcription factors. The PAX5 gene plays an important role in both cell differentiation as well as in embryonic development, and is located on chromosome 9p13. 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 33 publications
1
91
0
Order By: Relevance
“…Their data also showed that PAX5 fusion products suppressed transcriptional activity of PAX5 in a dominant-negative fashion (23). In addition, other researcher have reported PAX5 fusion genes, including PAX5 fused to ETV6 (12p13) (23,24), FOXP1 (3p14) (23), ZNF521 (18q11) (23), ELN (7q11.23) (25), and PML (15q24) (26). We have found PAX5 fused to either ETV6, FOXP1, C20orf112 (20q11), or AUTS2 (7q11.22).…”
Section: Discussionmentioning
confidence: 87%
“…Their data also showed that PAX5 fusion products suppressed transcriptional activity of PAX5 in a dominant-negative fashion (23). In addition, other researcher have reported PAX5 fusion genes, including PAX5 fused to ETV6 (12p13) (23,24), FOXP1 (3p14) (23), ZNF521 (18q11) (23), ELN (7q11.23) (25), and PML (15q24) (26). We have found PAX5 fused to either ETV6, FOXP1, C20orf112 (20q11), or AUTS2 (7q11.22).…”
Section: Discussionmentioning
confidence: 87%
“…Subsequent studies have identified additional PAX5 fusions in ALL, involving multiple partner genes including ASXL1, AUTS2, BRD1, C20orf112, DACH1, ELN, HIPK1, JAK2, KIF3B, LOC392027, PML, POM121 and SLCO1B3. 47,[63][64][65][66] The overall frequency of PAX5 translocations appears low (B2.6% B-ALL cases), 66 although studies comprehensively examining PAX5 translocation in large B-ALL cohorts are awaited. Genomic resequencing of PAX5 in the St Jude study described above also identified 16 missense, insertion/deletion, splice site and frameshift mutations that clustered in the key DNA-binding and transactivating domains of PAX5.…”
Section: Mutations Of Genes Regulating B-lymphoid Development In Allmentioning
confidence: 99%
“…By contrast, a dominant-negative action was established for PAX5-ELN, 16 PAX5-ETV6 11,12 and PAX5-FOXP1 12 fusions.…”
Section: Discussionmentioning
confidence: 99%
“…9 On the other hand, PAX5 translocations have also been associated with a block of early B-cell differentiation because the PAX5-ETV6 chimeric protein, product of the dic(9;12)(p13;p13), is associated with B-cell progenitor acute lymphoblastic leukemia (BCP-ALL). 11 Additional PAX5 fusion partner genes have been identified as HIPK1 (chromosomal band 1p13), [12][13][14] LOC392027 (7p12.1), 15 AUTS2 (7q11.1), 13 POM121 (7q11), 14 ELN (7q11), 16 JAK2 (9p24), 14 SLCO1B3 (12p12), 15 DACH1 (13q21), 14 PML (15q24), 17 ZNF521 (18q11.2), 12 ASXL1 (20q11.1), 15 C20orf112 (20q11.1), [13][14][15] KIF3B (20q11.21) 15 and BRD1 (22q13). 14 PAX5-ELN, 16 PAX5-FOXP1 12 and PAX5-ETV6 12 act as constitutive repressors of the remaining PAX5 allele product, explaining the block of B-cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation